Exploration of fMRI brain responses to oral sucrose after Roux-en-Y gastric bypass in obese yucatan minipigs in relationship with microbiota and metabolomics profiles. Issue 3 (March 2023) - Bergeat, Damien; Coquery, Nicolas; Gautier, Yentl; Clotaire, Sarah; Vincent, Émilie; Romé, Véronique; Guérin, Sylvie; Le Huërou-Luron, Isabelle; Blat, Sophie; Thibault, Ronan; Val-Laillet, David
Summary: Background & aims: In most cases, Roux-en-Y gastric bypass (RYGBP) is an efficient intervention to lose weight, change eating behavior and improve metabolic outcomes in obese patients. We hypothesized that weight loss induced by RYGBP in obese Yucatan minipigs would induce specific modifications of the gut–brain axis and neurocognitive responses to oral sucrose stimulation in relationship with food intake control. Methods: An integrative study was performed after SHAM (n = 8) or RYGBP (n = 8) surgery to disentangle the physiological, metabolic and neurocognitive mechanisms of RYGBP. BOLD fMRI responses to sucrose stimulations at different concentrations, brain mRNA expression, cecal microbiota, and plasma metabolomics were explored 4 months after surgery and integrated with WGCNA analysis. Results: We showed that weight loss induced by RYGBP or SHAM modulated differently the frontostriatal responses to oral sucrose stimulation, suggesting a different hedonic treatment and inhibitory control related to palatable food after RYGBP. The expression of brain genes involved in the serotoninergic and cannabinoid systems were impacted by RYGBP. Cecal microbiota was deeply modified and many metabolite features were differentially increased in RYGBP. Data integration with WGCNA identified interactions between key drivers of OTUs and metabolites features linked to RYGBP. Conclusion: This longitudinal study in the obese minipig model illustrates with a systemic and integrative analysis the mid-term consequences of RYGBP on brain mRNA expression, cecal microbiota and plasma metabolites. We confirmed the impact of RYGBP on functional brain responses related to food reward, hedonic evaluation and inhibitory control, which are key factors for the success of anti-obesity therapy and weight loss maintenance.